Constructivism learning theory: A paradigm for students' critical thinking, creativity, and problem solving to affect academic performance in higher education - Almulla, Mohammed Abdullatif (Cogent education, 2023)
This study looks at whether creativity and critical thinking help students solve problems and improve their grades by mediating the link between 21 st century skills (learning motivation, cooperativity, and interaction with peers, engagement with peers, and a smart classroom environment). The mediating relationship between creativity and critical thinking was discovered using structural equation modelling (SEM) research. The participants in the study were 297 postgraduate and undergraduate students from four faculties at King Faisal University who consented to take part. They were chosen using random sampling and volunteered to take part. Learning motivation, cooperativity, peer interaction, peer engagement, and a smart classroom environment all had a direct positive impact on students' critical thinking and creativity; their critical thinking and creativity had a direct positive impact on their problem solving and academic performance; and their problem solving had a direct positive impact on their academic performance. The hypotheses developed a model for measuring students' critical thinking and creativity, which affect problem-solving skills and thus students' academic performance in Saudi Arabian higher education.